1995
DOI: 10.1161/01.cir.92.3.415
|View full text |Cite
|
Sign up to set email alerts
|

Human Heart–Infiltrating T-Cell Clones From Rheumatic Heart Disease Patients Recognize Both Streptococcal and Cardiac Proteins

Abstract: The presence of heart-M protein cross-reactive T-cell clones in rheumatic heart lesions suggests their direct involvement in the pathogenesis of this disease. The dissection of protective and pathogenic epitopes of streptococcal M protein is an important step in allowing the development of a safe anti-streptococcal synthetic vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
188
0
23

Year Published

1997
1997
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(220 citation statements)
references
References 36 publications
9
188
0
23
Order By: Relevance
“…Yet over the years this hypothesis has disappointed many of its supporters as no pathogenetic relevance of the cross-reactive antibodies for causing organ damage was found. Only recently have data indicated that the pathogenetic principle inherent in this antigenic mimicry process is not mediated by cross-reactive antibodies, but rather by cross-reactive T lymphocytes that recognize the same epitopes as the antibodies: T-cell clones isolated from cardiac tissue of patients with poststreptococcal myocarditis responded to homologous peptides from both myosin and streptococcal M proteins, and these peptides corresponded to the epitopes recognized by cross-reactive antibodies from the same individuals [22].…”
Section: Group a Beta-haemolytic Streptococci -Several Ways To Contrimentioning
confidence: 99%
“…Yet over the years this hypothesis has disappointed many of its supporters as no pathogenetic relevance of the cross-reactive antibodies for causing organ damage was found. Only recently have data indicated that the pathogenetic principle inherent in this antigenic mimicry process is not mediated by cross-reactive antibodies, but rather by cross-reactive T lymphocytes that recognize the same epitopes as the antibodies: T-cell clones isolated from cardiac tissue of patients with poststreptococcal myocarditis responded to homologous peptides from both myosin and streptococcal M proteins, and these peptides corresponded to the epitopes recognized by cross-reactive antibodies from the same individuals [22].…”
Section: Group a Beta-haemolytic Streptococci -Several Ways To Contrimentioning
confidence: 99%
“…Streptococcus pyogenes and cardiac proteins recognized by these T lymphocytes has been shown by our group (GUILHERME L et al, 1995) and may explain the auto-aggressive phenotype of these lesions. RF is the most convincing example of molecular mimicry in humans which is able to trigger an autoimmune reaction and furthermore its etiologic agent is well characterized.…”
supporting
confidence: 56%
“…A reação cruzada celular por linfócitos T CD4 + infiltrantes das lesões cardíacas foi, inicialmente demonstrada pela reatividade de peptídeos da proteína M5 do estreptococo e proteínas derivadas do tecido valvular (GUILHERME L et al, 1995 , 2003).…”
Section: Histopatologiaunclassified
See 2 more Smart Citations